PENGARUH ORGANIZATIONAL LEARNING TERHADAP COMPETITIVE ADVANTAGE MELALUI ACCOUNTING INFORMATION SYSTEM PADA PERUSAHAAN MANUFAKTUR TERBUKA - Sheleen Wijaya (Business Accounting Review, 2015)
This study aimed to analyze the influence of organizational learning to competitive advantage through accounting information system. The samples used in this study were 60 managers who are working in a go-public manufacturing companies. The analysis technique was Structural Equation Model (SEM) by using Partial Least Square (PLS) software. The results from this study showed that there was a positive and significant correlation between the organizational learning to competitive advantage, organizational learning to accounting information system, and accounting information system to competitive advantage.